Does Taxation Rhyme with Democracy? - Zoido, Pablo (OECD Publishing, 2007)
Latin America has put its faith in democracy and the market economy. Efficient, fair and equitable fiscal policy can help foster development and consolidate democracy. * This Policy Insights is based on the Latin American Economic Outlook 2008
Keywords: Development